Pragmatic Role of Culture in Using Ostensible Invitations across Persian and English Languages - Nehal, Rashid (LingPoet: Journal of Linguistics and Literary Research, 2021)
I first begin with the definition of speech acts with a view to providing a distinction between the traditional and modern view of speech acts and then the focus will be on making the distinction between ostensible speech acts vs. genuine speech acts. Finally, my observation relates to the Ahmadi& Rasekh (2010) paper describing the pragmatic features of two culturally Persian culture, north and centre with respect to the use of genuine and ostensible invitations in English based on ten discourse situations and utterances chosen for data collection. The data is compared with the structure of invitations in English reported by Isaacs and Clark (1990). It is concluded that that the socio-linguistic factors might prove useful to understand better the dynamics of failure to recognize the correct function of speech acts in EFL educational settings since these difficulties are reported in Ahmadi and Rakesh’s paper.